Comprehensive construction strategy of bidirectional green tissue‐specific synthetic promoters. Issue 3 (19th August 2019) - Bai, Jiuyuan; Wang, Xin; Wu, Hao; Ling, Fei; Zhao, Yun; Lin, Yongjun; Wang, Rui
Summary: Bidirectional green tissue‐specific promoters have important application prospects in genetic engineering and crop genetic improvement. However, there is no report on the application of them, mainly due to undiscovered natural bidirectional green tissue‐specific promoters and the lack of a comprehensive approach for the synthesis of these promoters. In order to compensate for this vacancy, the present study reports a novel strategy for the expression regulatory sequence selection and the bidirectional green tissue‐specific synthetic promoter construction. Based on this strategy, seven promoters were synthesized and introduced into rice by agrobacterium ‐mediated transformation. The functional identification of these synthetic promoters was performed by the expression pattern of GFP and GUS reporter genes in two reverse directions in transgenic rice. The results indicated that all the synthetic promoters possessed bidirectional expression activities in transgenic rice, and four synthetic promoters ( BiGSSP2, BiGSSP3, BiGSSP6, BiGSSP7 ) showed highly bidirectional expression efficiencies specifically in green tissues (leaf, sheath, panicle, stem), which could be widely applied to agricultural biotechnology. Our study provided a feasible strategy for the construction of synthetic promoters, and we successfully created four bidirectional green tissue‐specific synthetic promoters. It is the first report on bidirectional green tissue‐specific promoters that could be efficiently applied in genetic engineering.